2018
DOI: 10.1103/physreva.97.012332
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for approximate additivity of the Holevo information of quantum channels

Abstract: We study quantum channels that are close to another channel with weakly additive Holevo information and derive upper bounds on their classical capacity. Examples of channels with weakly additive Holevo information are entanglement-breaking channels, unital qubit channels, and Hadamard channels. Related to the method of approximate degradability, we define approximation parameters for each class above that measure how close an arbitrary channel is to satisfying the respective property. This gives us upper bound… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
104
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 92 publications
(104 citation statements)
references
References 83 publications
0
104
0
Order By: Relevance
“…As one of the last technical developments of our paper, we address the question of computing energyconstrained channel distances in a very broad sense, by considering the energy-constrained, generalized channel divergence of two quantum channels, as an extension of the generalized channel divergence developed in [LKDW18]. In particular, we prove that an optimal Gaussian input state for the energy-constrained, generalized channel divergence of two particular Gaussian channels is the two-mode squeezed vacuum state that saturates the energy constraint.…”
Section: Summary Of Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As one of the last technical developments of our paper, we address the question of computing energyconstrained channel distances in a very broad sense, by considering the energy-constrained, generalized channel divergence of two quantum channels, as an extension of the generalized channel divergence developed in [LKDW18]. In particular, we prove that an optimal Gaussian input state for the energy-constrained, generalized channel divergence of two particular Gaussian channels is the two-mode squeezed vacuum state that saturates the energy constraint.…”
Section: Summary Of Resultsmentioning
confidence: 99%
“…We finally used the generalized channel divergence from [LKDW18] to address the question of optimal input states for the energy-bounded diamond norm and other related divergences. In particular, we showed that for two Gaussian channels that are jointly phase and displacement covariant, the Gaussian energy-constrained generalized channel divergence is achieved by a two-mode squeezed vacuum state that saturates the energy constraint.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recalling the definition of the channel mana in terms of the discrete Wigner function (see (61)) and abbreviating X CPWP as Ξ, consider that…”
Section: Amortization Inequalitymentioning
confidence: 99%
“…Examples of generalized divergences, in addition to the trace distance and relative entropy, include the Petz-Rényi relative entropies [56], the sandwiched Rényi relative entropies [57,58], the Hilbert α-divergences [59], and the c 2 divergences [60]. One can then define the generalized channel divergence [61], as a way of quantifying the distinguishability of two quantum channels   A B and   A B , as follows:…”
Section: Generalized Thauma Of a Quantum Channelmentioning
confidence: 99%